Health Insurance and Poverty in Trajectories of Out‐of‐Pocket Expenditure among Low‐Income Middle‐Aged Adults - Kwon, Eunsun (Health Serv Res, 2018)
OBJECTIVE: To assess the effects of longitudinal patterns of health insurance and poverty on out‐of‐pocket expenditures among low‐income late middle‐aged adults. DATA SOURCES/STUDY SETTING: Six waves (2002–2012) of the Health and Retirement Study, in combination with RAND Center for the Study of Aging data, were used. STUDY DESIGN: A random coefficient regression analysis was conducted in a multilevel growth curve framework to estimate the impact of health insurance and poverty on out‐of‐pocket expenditures. PRINCIPAL FINDINGS: At baseline, individuals with private insurance or unstable coverage were more likely to have out‐of‐pocket expenditures and financial burdens than public insurance holders. Over time, the poor who had no insurance, unstable coverage, or insurance type change had higher out‐of‐pocket expenditures; private coverage holders had higher odds of financial burden. CONCLUSIONS: Unstable insurance coverage had a discernible effect on the long‐term, out‐of‐pocket expenditures among low‐income adults. Findings have an important policy implication to protect poor late middle‐aged population; as this population enters old age, the high financial burden it faces may exacerbate persistent socioeconomic health disparity among older people with unstable insurance coverage.